Genetics of cluster bearing habit and fruit surface morphology in ridge gourd (Luffa acutangula Roxb.) - Karmakar, Pradip; Munshi, AD (Vegetable Science, 2023)
Luffa acutangula or ridge gourd generally produces solitary and ribbed or ridged fruit, but Satputia a feral form of ridge gourd withhermaphrodite sex form produces non-ribbed fruits in cluster. The present study was conducted to determine the inheritance clusterbearing habit and non-ridge fruit in ridge gourd from the crosses of two hermaphrodite lines (Satputia Long and Satputia Small) whichproduced small numerous non-ribbed fruits in cluster and five monoecious lines (DRG-2, Pusa Nasdar, Utkal Tripti, Arka Summet andHARG-110), produced solitary long fruit with ten prominent ridges. It was observed that all the F1 plants were solitary bearer andproduced ridged fruit. In F2 generation, the observed distribution of plant phenotypes for bearing habit and fruit surface morphologyfitted well to the expected ratio of 3:1 (solitary vs cluster) and 15:1 (ridge vs non-ridge) for bearing habit and fruit surface morphology,respectively. The segregation pattern suggested monogenic recessive control of cluster bearing habit, while duplicate recessive genescontrol ridged fruit surface in Luffa acutangula.